Slovenski prevod prenovljene lestvice telesne samopodobe oseb po amputaciji (ABIS-R) - Rutar, Miha (Rehabilitacija (Ljubljana), 2021)
Background: Amputation of body part drastically interferes with the body image, which is significantly related to psychological adaptation to amputation, therefore it is important to measure it. As we do not have a suitable instrument for measuring the body image of people with lower-limb amputation in Slovenia, we decided to translate The Amputation Body Image Scale Revised (ABIS-R), which is the most frequently used instrument for measuring body image after amputation in the world. Methods: The scale was translated according to the guidelines for translation of psychological instruments: three experts independently translated original English version of the scale into Slovenian, a consolidated Slovenian translation was then translated back into English by a fourth expert, and both English translators were compared and the necessary adjustments were made. The scale was then administered to 16 patients with lower-limb amputation, who commented on specific items. Results: After comparing the two English versions, the authors changed the item seven. The administration of the scale on the pilot group showed that in general patients had no difficulty in responding. A closer examination of the items showed an ambiguous understanding of item twelve, which was then adjusted. Conclusion: The ABIS-R translation in the pilot sample generally proved to be understandable and suitable for Slovenian people with lower-limb amputation and therefore represents a valuable tool in clinical work. In the next steps, it is necessary to administer the scale on a larger sample of patients for further validation and psychometric studies.
Keywords: ABIS-R; amputacija; Amputation; body image; Prenovljena lestvica telesne samopodobe oseb po amputaciji; psychology; telesna samopodoba; The Amputation Body Image Scale Revised